Activity of Liquid Smoke of Tobacco Stem Waste as An Insecticide on Spodoptera litura Fabricius Larvae - Heri Prabowo; Edhi Martono; Witjaksono Witjaksono (Universitas Gadjah Mada, 2016)
The use of chemical insecticide in crop protection around the world has resulted in disturbances of the environment. Therefore, it is necessary to develop for environmentally friendly insect pest management techniques such as the activity of liquid smoke made from tobacco stem waste as an insecticide to Spodoptera litura. Activity of liquid smoke of tobacco stem waste was carried out at the laboratory condition. The results showed that the application of liquid smoke by using the spraying method (direct method) showed better results compared to the results of feeding method (indirect method). Lethal concentration (LC) at 5 days after treatment, LC50 and LC75 values the direct method of 2.9% and 8.87%, while the indirect method of 6,99% and 21.03%. The sub lethal concentration did not cause mortality of S. litura larvae, but inhibited the growth such as indicated by lower weight of larval and pupal in treated larvae than in control. Liquid smoke of tobacco stem waste has activity as an insecticide to S. litura. INTISARIPenggunaan pestisida kimia dalam pengendalian hama di dunia telah menimbulkan gangguan terhadap lingkungan. Maka teknik pengendalian hama yang ramah lingkungan perlu dikembangkan, misalnya aktivitas asap cair limbah batang tembakau sebagai insektisida pada Spodoptera litura. Aktivitas asap cair limbah batang tembakau dilakukan pada kondisi laboratorium. Hasil penelitian menunjukkan bahwa aplikasi asap cair secara langsung (metode semprot) lebih efektif daripada tidak langsung (metode celup pakan). Lethal concentration (LC) pada 5 hari setelah perlakuan, LC50 dan LC75 pada aplikasi langsung sebesar 2,9% dan 8,87%, sedangkan pada aplikasi tidak langsung 6,99% dan 21,03%. Konsentrasi subletal tidak menyebabkan kematian S. litura tetapi mampu menghambat pertumbuhan yang diindikasikan dengan rendahnya bobot larva dan pupa S. litura. Asap cair limbah batang tembakau bersifat insektisida terhadap larva S. litura.